Representasi Pelecehan Seksual dan Kekerasan Seksual KBGO dalam Film “Sleep Call” - Kusuma, Anggun Dila; Urfan, Noveri Faikar (Unitri Press, 2024)
Sexual harassment and sexual violence of KBGO in Indonesia is increasing, especially since the Covid-19 case. In addition, cases of sexual harassment or sexual violence are also very common in social reality and various sectors, whether in the realm of education or even the work environment. Through film, which is one of the containers used to describe the situation on social reality in society, it is able to convey the message contained in the film as a communication medium for the audience. The film Sleep Call is one of the films that raises the issue of sexual harassment and sexual violence against women by KBGO. In the film, it is depicted that sexual harassment and sexual violence in KBGO occur due to the existence of power relations with people who are labeled vulnerable, namely women. The researcher uses a qualitative-descriptive methodology as a research approach and uses a semiotic analysis method by taking symbols and texts used as the object of study, so that they must interpret and understand the codes in the signs and texts in the film. Data collection was carried out by observation and documentation techniques. The results of this study show that the representation of sexual harassment and sexual violence in KBGO experienced by women in films shows various categories of sexual harassment and sexual violence in KBGO which occurs due to power relations. Abstrak Pelecehan seksual dan kekerasan seksual KBGO di Indonesia semakin meningkat apalagi semenjak kasus Covid-19. Selain itu, kasus pelecehan seksual atau kekerasan seksual juga masih sangat sering terjadi di realitas sosial dan berbagai sektor entah itu di ranah pendidikan bahkan lingkungan pekerjaan. Melalui film yang menjadi salah satu wadah digunakan untuk menggambarkan situasi pada realitas sosial dimasyarakat mampu menyampaikan pesan yang terkandung dalam film sebagai media komunikasi untuk penonton. Film Sleep Call menjadi salah satu film yang mengangkat isu pelecehan seksual dan kekerasan seksual KBGO terhadap perempuan. Dalam film tersebut tergambar bahwa pelecehan seksual dan kekerasan seksual KBGO terjadi akibat adanya relasi kuasa terhadap kaum yang dicap rentan yaitu perempuan. Peneliti menggunakan metodologi kualitatif-deskriptif sebagai pendekatan penelitian serta menggunakan metode analisis semiotika dengan mengambil simbol dan teks yang digunakan sebagai objek kajian, sehingga harus menafsirkan dan memahami kode-kode yang ada pada tanda dan teks dalam film. Pengumpulan data dilakukan dengan teknik observasi dan dokumentasi. Hasil penelitian ini menunjukan bahwa representasi pelecehan seksual dan kekerasan seksual KBGO yang dialami perempuan dalam film menunjukan berbagai kategori pelecehan seksual dan kekerasan seksual KBGO yang terjadi akibat relasi kuasa.